Regulation of ENaC in mice lacking renal insulin receptors in the collecting duct - Pavlov, Tengis S. (Federation of American Societies for Experimental Biology, 2013)
The epithelial sodium channel (ENaC) is one of the central effectors involved in regulation of salt and water homeostasis in the kidney. To study mechanisms of ENaC regulation, we generated knockout mice lacking the insulin receptor (InsR KO) specifically in the collecting duct principal cells. Single-channel analysis in freshly isolated split-open tubules demonstrated that the InsR-KO mice have significantly lower ENaC activity compared to their wild-type (C57BL/6J) littermates when animals were fed either normal or sodium-deficient diets. Immunohistochemical and Western blot assays demonstrated no significant changes in expression of ENaC subunits in InsR-KO mice compared to wild-type littermates. Insulin treatment caused greater ENaC activity in split-open tubules isolated from wild-type mice but did not have this effect in the InsR-KO mice. Thus, these results suggest that insulin increases ENaC activity via its own receptor affecting the channel open probability. To further determine the mechanism of the action of insulin on ENaC, we used mouse mpkCCD(c14) principal cells. Insulin significantly augmented amiloride-sensitive transepithelial flux in these cells. Pretreatment of the mpkCCD(c14) cells with phosphatidylinositol 3-kinase (LY294002; 10 μM) or mTOR (PP242; 100 nM) inhibitors precluded this effect. This study provides new information about the importance of insulin receptors expressed in collecting duct principal cells for ENaC activity.—Pavlov, T. S., Ilatovskaya, D. V., Levchenko, V., Li, L., Ecelbarger, C. M., Staruschenko, A. Regulation of ENaC in mice lacking renal insulin receptors in the collecting duct.